Field Station Bahia - Sansone, Livio (Brill, 2023)
This book offers a new perspective on the making of Afro-Brazilian, African-American and African studies through the interrelated trajectory of E. Franklin Frazier, Lorenzo Dow Turner, Frances and Melville Herskovits in Brazil. The book compares the style, network and agenda of these different and yet somehow converging scholars, and relates them to the Brazilian intellectual context, especially Bahia, which showed in those days much less density and organization than the US equivalent. It is therefore a double comparison: between four Americans and between Americans and scholars based in Brazil.